Effects of anti-scaling and cleaning chemicals on membrane scale in direct contact membrane distillation process for RO brine concentrate - Peng, Y.; Ge, J.; Li, Z.; Wang, Shaobin (Elsevier, 2015)
Membrane distillation (MD) is a promising desalination technology for water recovery from reverse osmosis (RO) brine. However, calcium sulfate as the major pollutant in RO brine concentrates induces scale occurrence in MD. Effective control of membrane scaling and cleaning of the membrane module are the key technologies for the industrialization of MD. In this work, effects of four anti-scaling and five cleaning agents on calcium sulfate scaling in direct contact membrane distillation (DCMD) process were investigated and discussed. It was found that membrane scaling and wetting was significantly alleviated with the addition of an effective anti-scaling agent. The flux recovery of a membrane with five cleaning agents was also improved and the flux recovery using a 2% EDTA-4Na solution was obtained as high as 92.8% at 77 °C.